Alternative splicing of caspase-8 mRNA during differentiation of human leukocytes - Eckhart, Leopold; Krammer, Peter H. (Biochemical and biophysical research communications, 2001)
Caspase-8 is a key initiator of death receptor-induced apoptosis. Here we provide evidence that caspase-8 expression is subject to posttranscriptional regulation in human leukocytes. Resting peripheral blood lymphocytes preferentially use a distant splice donor site at the 3′-end of caspase-8 exon 8 to generate mRNAs with a truncated open reading frame. When lymphocytes were activated, the expression of caspase-8 variants was shifted to caspase-8/a and b which lack the extension of exon 8. The opposite change of the splicing pattern was found in a neutrophil differentiation model. Promyelocytic HL-60 cells mainly expressed caspase-8 mRNAs with the normal exon 8, but the splicing pattern was changed to the distant exon 8 splice site during DMSO-induced differentiation of HL-60 cells. In spite of the presence of these novel mRNAs, the corresponding translation products were not detectable in either cell type. Our findings suggest that leukocyte differentiation and alternative splicing of caspase-8 pre-mRNA are inter-dependent processes.